2008
DOI: 10.1042/ba20070107
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐interference‐mediated Cdc42 silencing down‐regulates phosphorylation of STAT3 and suppresses growth in human bladder‐cancer cells

Abstract: Cdc42 (cell division cycle 42), a member of Rho GTPases, is involved in cell transformation, proliferation, survival, invasion and metastasis of human cancer cells. Here, RNAi (RNA interference)-mediated gene silencing was used to investigate the roles of Cdc42 and to assess its therapeutic potential in human bladder cancer. The results showed that Cdc42 silencing resulted in a marked reduction of Cdc42 mRNA and protein expression and a significant inhibition of cell proliferation from G(0)/G(1)- to S-phase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
4
10
0
Order By: Relevance
“…In contrast, downregulation of Cdc42 signals can inhibit anchorage-independent growth and induce apoptosis via the PI(3)K-Akt and Erk signaling cascades and the p53 tumor suppressor (8). Consistent with these reports, Cdc42 silencing by small hairpin RNA was able to reverse the metastatic and growth behavior of human colorectal cancer cells and bladder cancer cells (9,10). Taken together, the observed effects of Cdc42 over-expression and silencing on the cell malignant transformation indicate a role for Cdc42 in regulating tumor metastasis and progression.…”
Section: Introductionsupporting
confidence: 77%
“…In contrast, downregulation of Cdc42 signals can inhibit anchorage-independent growth and induce apoptosis via the PI(3)K-Akt and Erk signaling cascades and the p53 tumor suppressor (8). Consistent with these reports, Cdc42 silencing by small hairpin RNA was able to reverse the metastatic and growth behavior of human colorectal cancer cells and bladder cancer cells (9,10). Taken together, the observed effects of Cdc42 over-expression and silencing on the cell malignant transformation indicate a role for Cdc42 in regulating tumor metastasis and progression.…”
Section: Introductionsupporting
confidence: 77%
“…In a study by Zins et al (21) it was demonstrated that a Ras-related C3 botulinum toxin substrate 1/Cdc42 GTPase-specific small molecule inhibitor could effectively suppress the growth of primary human prostate cancer xenografts and prolong survival in mice. Furthermore, it has been reported that Cdc42 expression is significantly upregulated in bladder cancer tissues compared with that in normal tissues, and Cdc42 silencing caused by siRNA can inhibit the phosphorylation of STAT3 and suppress the growth of bladder cancer cells, suggesting that Cdc42 may serve as a therapeutic target for the treatment of bladder cancer (22,14). In the present study, it was demonstrated that miR-195 upregulation could inhibit Cdc42 protein expression in bladder cancer T24 cells.…”
supporting
confidence: 48%
“…As Cdc42/STAT3 signaling has been found to largely contribute to bladder cancer cell proliferation (14), and miR-195 can inhibit the protein expression of Cdc42 in bladder cancer T24 cells, we speculated that miR-195 could play a suppressive role in bladder cancer cell proliferation, via downregulation of Cdc42/STAT3 signaling. To verify this theory, bladder cancer T24 cells were transfected with miR-195 mimics or Cdc42-specific siRNA, or co-transfected with miR-195 mimics and Cdc42 plasmid, respectively.…”
Section: Cdc42/stat3 Signaling Is Involved In the Mir-195-mediated Inmentioning
confidence: 99%
“…5B). Notably, silencing of CDC42 is lethal in Candida (39) and inhibits the growth of mammalian cells (70). More importantly, Cdc42p (cell division cycle 42) is involved in C. albicans filament-specific characteristics, including hyphal growth and filament-specific gene transcripts (12,68,73).…”
Section: Discussionmentioning
confidence: 99%